A study on the surface responses and degradation mechanisms of epoxy-amine coating subjected to UV accelerated weathering and hygrothermal ageing using ToF-SIMS and FTIR analysis - Ng, Janice Xin Yee; Tan, Nicholas Sheng Loong; Chung, W.H.; Golovanevskiy, Vladimir; Farhat, H.; Pojtanabuntoeng, Thunyaluk (2024)
Epoxy amine coatings were subjected to hygrothermal ageing and accelerated weathering conditions that is comprised of neutral salt spray test and UV accelerated degradation condition. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) and Fourier Transform Infrared Spectroscopy (FTIR) were employed to study the surface responses and spectral variation of epoxy amine coatings subjected to different ageing conditions. As a result, principal component analysis (PCA) of ToF-SIMS positive ion spectra illustrated that principal component 1 (PC1) has collected information on a variation of surface responses caused by accelerated weathering and hygrothermal ageing conditions as compared to fresh epoxy amine coatings. On the other hand, principal component 2 (PC2) has distinguished the different surface responses generated on epoxy amine coatings that were subjected to UV accelerated degradation conditions and those that were not. FTIR analysis has demonstrated the hydrolysis and photooxidation of epoxy amine coatings from the growth of two absorption bands at 1709 cm−1 and 1650 cm−1, indicating the formation of carbonyl-containing groups such as ketones, aldehydes, phenyl formates, imine or tertiary amides. This comprehensive analysis provides significant insights into the degradation mechanisms of epoxy amine coatings subjected to corrosion under insulation (CUI) and/or artificial weathering (AW) environment. Understanding these mechanisms is pivotal for industries reliant on epoxy coatings, such as oil and gas, ensuring enhanced performance and extended lifespan of their products under varying environmental conditions. The findings also contribute to the broader field of materials science by offering methodologies and analytical approaches that can be applied to other polymeric coatings and materials.